PG83 Evaluating the impact of integrating intersectionality into simulation training on healthcare outcomes. (10th November 2020) - Ogonah, Maya; Pathan, James; Iannelli, Hannah; Cross, Sean; Novogrudsky, Kat
Abstract : As individuals, different aspects of our identity – for example, our class, race, sexual orientation and gender presentation – are subject to social stratification. Intersectionality seeks to identify how different forms of discrimination, based on identity axes, are related to one another and how their intersection influences social and political equity, including healthcare outcomes. Research suggests inequities, caused by interactions between consumer and healthcare providers (e.g. patronising doctors) and macroenvironmental dynamics such as discriminatory healthcare policies, create deep segregations between the treatment of dominant and marginalised groups in the provision of healthcare. 1 Thus, simulation training courses which address how the intersection of different identity axes can influence healthcare outcomes are necessary to ensure an equitable level of care is provided to all patients. This poster presentation seeks to evaluate how simulation training can be used to address interactions between healthcare professionals and simulated mental health patients with different intersectional identity axes. The new conceptual model requires that simulation training courses include simulated patients from varying racial and socio-economic backgrounds with complex character backstories which involve further intersectional social identities. It is key that training courses include simulated patients of different backgrounds, as the presentation of mental illness can differ based on religious, spiritual, or cultural factors. For example, the development of eating disorder symptomatology differs in adolescent boys compared to adolescent girls 2 – gender affects the presentation. Further, cultural factors, such as the idolisation of particular body shapes, are also likely to influence the development and presentation of eating disorders. Thus, by including simulated patients of different backgrounds, healthcare professionals can learn how the presentation of mental illnesses differs dependent on the patient's identity axes. This is likely to have a positive effect on patient outcomes as mental health issues may be less likely to remain undiagnosed since professionals are aware of all the varying types of presentation. Further, including a diverse range of simulated patients is an achievable objective with minimal additional costs and large potential benefits Thus far, the literature lacks research investigating the incorporation of intersectionality into simulated healthcare training and how this can affect mental health outcomes. This poster presentation posits that simulation training is an effective vehicle for educating healthcare professionals on the nuances of intersectionality and plans to detail how including diverse simulated patients impacts debriefs and informs a greater understanding of patient's needs, which in turn impacts practice and patient outcomes. References: Corus C. & Saatcioglu B. An intersectionality framework for transformative services research. The Service Industries Journal 2015;35:7–8, 415–429. Verschueren M., Laurence C, Palmeroni N, Bogarts A, Gandhi A, Moons P, & Luyckx K. Eating disorder symptomatology in Adolescent Boys and Girls: Identifying Distinct Developmental Trajectory Classes. The Journal of Youth and Adolescence 2019;49:410–426.